THE PHYSICAL MEANING OF THE TITIUS-BODE FORMULA - Smirnov, V. A. (Одеські астрономічні публікації, 2016)
It is proposed an special hypothesis of the formation of symmetric objects in space with the help of the interference of standing waves which act in the process of evolution of the primordial gas-dust cloud including the formation of the Solar system, that may be revealed by 11-year cycle of Solar activity in particular. It is used the idea of J.Kepler of the construction of the Solar system, viewed as inscribed and circumscribed Platonic figures, a common measure of which, according to the author, is the length of the standing waves generated by the variable energy sources of the primary cloud. This explains the physical meaning of the Titius-Bode formula. In 1968 S.F.Dermott revealed the foundation of Titius-Bode empiric formula, basing on Theory of Resonance. But in addition to direct statement of existing resonance mechanism of formula T(n)=T(0)*Cn, n=1,2,3,4, physical sense does not come to light. I tried to explain the formation of symmetric figures and space constructions with evident experience of formation of Chladni E. figures, offering the calculation, confirmed by experience of appearance of new space bodies in the nodes of standing waves of primary gas-dust cloud. The interference of standings waves is surely promotes the formation of different figures – such as symmetric galaxies, hexagon vortex at Saturn, and others. Unlike Dermott’s theory, our explanation of symmetric formation of planets is a common solution of task for multi bodies interaction, and proposes the version of solution in case with more than two bodies.